2018
DOI: 10.1093/geroni/igy030
|View full text |Cite
|
Sign up to set email alerts
|

Coming Out of “Retirement”—Predictors of Driving Resumption Among Older Drivers

Abstract: Background and ObjectivesPredictors and consequences of driving cessation in older adults have been studied extensively. This study sought to establish the extent to which former drivers resume driving and identify associated factors.Research Design and MethodsDescriptive analysis of the 2011–2015 National Health and Aging Trends Study data (Round 1: n = 6,680; Round 5: n = 3,409) characterized the extent of driving resumption through 2015 by baseline driving status (driver, former driver, never driver). Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…For "environmental factors", Finestone et al [2] reported that people who resumed driving after a stroke were more likely to rely on friends, family, public transport, and taxis than those who did not resume driving. Kendra [27] reported that elderly drivers with greater impairment to mode of transport showed a statistically significantly increased likelihood of resuming driving. Another study in elderly patients reported [28] that those with a limited social network were more likely to resume driving, whereas adequate support from family and friends was linked with driving cessation.…”
Section: Data Collectionmentioning
confidence: 99%
“…For "environmental factors", Finestone et al [2] reported that people who resumed driving after a stroke were more likely to rely on friends, family, public transport, and taxis than those who did not resume driving. Kendra [27] reported that elderly drivers with greater impairment to mode of transport showed a statistically significantly increased likelihood of resuming driving. Another study in elderly patients reported [28] that those with a limited social network were more likely to resume driving, whereas adequate support from family and friends was linked with driving cessation.…”
Section: Data Collectionmentioning
confidence: 99%